Determination of river water level triggering flood in Manghinao River in Bauan, Batangas, Philippines / C E F Monjardin ... [et al.] - Monjardin, C E F; Transfiguracion, K M; Mangunay, J P J; Paguia, K M; Uy, F A A; Tan, F J (Universiti Teknologi MARA, 2021)
Flooding is one of the problems experienced by many countries no matter what their economic status is. Even rich and developed countries experience it too. Flooding is mainly caused by natural events such as typhoons and monsoon rains even anthropogenic causes that sometimes could not be stopped even if there are flood control structures in place. The Philippines is located in the Pacific Ring of Fire and is visited by an average of 20 typhoons each year. People are used to experiencing flooding and it is about time that we somehow do something about it. There have been many technologies available right now that could aid us to improve our capability to adapt to such phenomena. Heavy precipitation is usually experienced during the monsoon season that leads to severe flooding in a specific area. The application of HEC-RAS (Hydrologic Engineering Centre's River Analysis System) Modelling Software was used in the study in Manghinao River for comprehensive hazard mapping and risk assessment in the downstream area of the Bauan River for 100-year return period flood. 2D flood hazard simulation was done and the river water level that would trigger flooding downstream was identified. At 0.5 m of flood height, people are considered immobilized to move from one place to another so the best time to evacuate people is before the flood reaches that level. Results showed that LGU has 4 hours to evacuate people starting when the river water at the gaging station reads 0.5 m, this gives them enough time to give warning and ask people to move to evacuations sites to prevent them being stranded in their houses. This study can support future planning and for the development of flood control plans and flood mitigation measures to minimize the losses due to flood disasters in Batangas Province, Philippines particularly in the Bauan area.